2014
DOI: 10.1002/ece3.1272
|View full text |Cite
|
Sign up to set email alerts
|

The application of eDNA for monitoring of the Great Crested Newt in the UK

Abstract: Current ecological surveys for great crested newts are time-consuming and expensive and can only be carried out within a short survey window. Additional survey methods which would facilitate the detection of rare or protected species such as the great crested newt (Triturus cristatus) would be extremely advantageous. Environmental DNA (eDNA) analysis has been utilized for the detection of great crested newts in Denmark. Here, the same methodology has been applied to water samples taken from UK ponds concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 41 publications
2
74
0
Order By: Relevance
“…For example, eDNA assays have been used to detect the eastern hellbender (Cryptobranchus a. alleganiensis), an amphibian of high conservation concern, in Indiana and Missouri, USA (Olson et al 2012). In the UK, eDNA assays have been validated for detection of the threatened great crested newt Triturus cristatus (Rees et al 2014a). Sigsgaard et al (2015) reported that eDNA surveys for endangered fish in Denmark outperformed traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, eDNA assays have been used to detect the eastern hellbender (Cryptobranchus a. alleganiensis), an amphibian of high conservation concern, in Indiana and Missouri, USA (Olson et al 2012). In the UK, eDNA assays have been validated for detection of the threatened great crested newt Triturus cristatus (Rees et al 2014a). Sigsgaard et al (2015) reported that eDNA surveys for endangered fish in Denmark outperformed traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Multimethod species distribution modelling or site occupancy modelling is one example for how this can be achieved and has been demonstrated in cases comparing qPCR for a single species and conventional methods (Hunter et al, 2015;Rees, Bishop, Middleditch, et al 2014;Schmelzle & Kinziger, 2016;Schmidt, Kery, Ursenbacher, Hyman, & Collins, 2013), but rarely for eDNA metabarcoding . Thus, we expect the robustness of eDNA metabarcoding to reveal species richness estimates for animals and plants will be improved by coupling distribution or occupancy modelling with studies to determine the scale of inference in space and time for an eDNA sample (Figure 1).…”
Section: Molecular Operational Taxonomic Unit (Motu)mentioning
confidence: 99%
“…Most of these studies investigated the presence of fish, including Chinook salmon (Oncorhynchus tshawytscha; Laramie et al 2015), brook and bull trout (Salvelinus fontinalis and S. confluentus; Wilcox et al 2013), and slackwater darter (Etheostoma boschungi; Janosik & Johnston 2015), as well as amphibians such as the great crested newt (Triturus cristatus; Rees et al 2014;Biggs et al 2015), Idaho salamander (Dicamptodon aterrimus), Rocky Mountain tailed frog (Ascaphus montanus; Goldberg et al 2011;Pilliod et al 2013) and eastern hellbender (Cryptobranchus alleganiensis alleganiensis; Olson et al 2012;Spear et al 2015). With the exception of the bull trout and slackwater darter, which are respectively classified as vulnerable and endangered (IUCN Red List version 2.3), these organisms may be locally rare, but are otherwise classified as low risk in terms of their conservation status.…”
Section: Studies Conducted On Rare Organismsmentioning
confidence: 99%
“…Jerde et al 2013;Takahara & Minimoto 2013), amphibians (e.g. Goldberg et al 2011;Olson et al 2012;Rees et al 2014), and invertebrates (e.g. Goldberg et al 2013;Machler et al 2014).…”
Section: Study Environmentsmentioning
confidence: 99%